Designing a Spreadsheet-Based Reverse Vending Machine (RVM) Database Using Arduino Mega 2560 and NodeMCU with App Script Integration - Nerissa Arviana Putri; Arniel Ahmad Rivai; Rifki Athaya; Mohamad Ramdhani; Dien Rahmawati (Jurnal Serambi Engineering, 2024)
This research discusses the database design for a spreadsheet based payment system using Arduino Mega 2560 and NodeMCU ESP8266 with the help of an app script on a Reverse Vending Machine (RVM) with non-cash rewards. The payment process on the RVM requires admin assistance, so a platform is needed to store data, including the user's mobile phone number and the rewards the user has received. The database allows administrators to check this data to process reward payments to users. Spreadsheet is the platform the author chose for the database because it is easy to use and flexible. Designing a spreadsheet as a database using serial communication between Arduino Mega 2560 and NodeMCU ESP8266. Apart from this, the design also requires the help of the App Script feature to store the user's mobile phone number data and rewards received in a spreadsheet. The design results show that this database is effective and efficient in connecting the RVM with a spreadsheet to store data, thereby reducing the administrative workload in the payment process from the RVM